Incorporating Indigenous Knowledge Systems into Collaborative Governance for Water: Challenges and Opportunities - von der Porten, Suzanne; de Loë, Rob E.; McGregor, Deborah (Osgoode Digital Commons, 2016)
The importance of Indigenous knowledge systems for environmental decision-making is now widely recognized. In the context of collaborative approaches to environmental governance, scholars and practitioners have recognized that Western knowledge is not sufficient, and that ideas, practices, and knowledge from Indigenous peoples is essential. Collaborative environmental governance practice tends to make assumptions about how Indigenous knowledge systems can be incorporated into decision-making without reflecting satisfactorily on contrasting perspectives of Indigenous peoples themselves; these perspectives are partially captured in the Indigenous governance literature. This essay draws on empirical research in British Columbia, a place where First Nations have been approached by organizations involved in water governance to be involved in collaborative decision-making. The research reveals an important disconnect between the perspectives of Indigenous knowledge-holders and the people promoting “integration” of this knowledge into collaborative decision-making processes. We offer suggestions for reconciling collaborative approaches to water governance with Indigenous knowledge systems and the values and perspectives of Indigenous peoples.